(untitled) (Colloquia Comparativa Litterarum, 2025)
Bulgarian Literature as World Literature, Edited by Mihaela P. Harper and Dimitar Kambourov, New York: Bloomsbury Academic, 2020, iv + 283 pp. ISBN: HB: 978-1-5013-4810-5; ePDF: 978-1-5013-4812-9; eBook: 978-1-5013- 4811-2.